THERMODYNAMICS OF TEXTILE CATIONIC DYE ADSORPTION ON CLINOPTILOLITE - AMIN, Goran; KONSTANTINOVIC, Sandra; JORDANOV, Igor; DJORDJEVIC, Dragan (Studia Universitatis Babeș-Bolyai Chemia, 2023)
This paper studies the thermodynamics of the adsorption of textile dye on clinoptilolite in order to estimate the potential of this natural material for decolorization. The adsorption of dye in the state of equilibrium in conditions of varying temperature, as well as different models of thermodynamic equilibrium, were analyzed. The most present mineral phase of the adsorbent is the mineral clinoptilolite with a mineral content of about 85% in the tuff. The natural adsorbent, clinoptilolite, originally from Serbia, was characterized by chemical analysis, and dominated by SiO2 (59.57%). The surface morphology was monitored by electron microscopy. In the research, the concentration of the textile cationic dye (10-110 g×dm-3) and the adsorption temperature (293-333 K) were varied, while the amount of clinoptilolite was constant (1 g). To characterize the equilibrium adsorption, the dye removed and the amount of adsorbed dye were calculated. In adsorption thermodynamics, several models have been studied to calculate the most important thermodynamic parameters, free energy change, enthalpy, and entropy change, depending on the choice of thermodynamic equilibrium constant. The activation energy and sticking probability were calculated using a modified Arrhenius–type equation.